Relationship between nutritional status, lifestyle and prognosis in patients diagnosed with COVID-19 hospitalized in the state of Pernambuco - Maria Bárbara Galdino Silva; Claudia Porto Sabino Pinho; João de Araújo Barros Neto; Marina de Moraes Vasconcelos Petribú; Keila Fernandes Dourado; Regiane Maio (Hospital de Clínicas de Itajubá, 2022)
Objective: To analyze the relationship between nutritional status and lifestyle habits and the prognosis of hospitalized patients with COVID-19 in Pernambuco. Methods: Multicenter, cross-sectional study, associated with prospective analysis variables, involving patients with COVID-19 and admitted to 8 hospitals. Individuals aged ≥ 18 years of both sexes, hospitalized from June 2020 to June 2021, were included. Socioeconomic, clinical, anthropometric, lifestyle and prognostic variables were collected. Results: The sample consisted of 263 individuals with a mean age of 62.9 ± 16.6 years and homogeneous distribution between genders. It was observed that 8.2% were smokers, 20.9% reported alcohol consumption, and 80.1% were sedentary. The anthropometric profile indicated that 49.5% were overweight and 7.0% were underweight. Malnutrition and excess weight were associated with more extended hospital stays (66.7% weight loss and 64.5% weight gain vs. 30.0% eutrophy; p = 0.021), smoking with death (tab 65 .0% vs. non-tab 33.7%; p = 0.006) and need for admission to the intensive care unit (yes 64.3%, no 31.5%; p = 0.014). The frequency of dyspnea was higher in patients who reported drinking alcohol (yes 69.6% vs. no 48.1%; p = 0.007). Physical activity was not associated with any prognostic factor. Conclusion: Nutritional extremes and bad lifestyle habits, such as smoking and alcohol consumption, are risk factors for a poor prognosis in individuals with COVID-19.